(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The food industry has undergone major changes in recent decades. Due to technological progress, the expansion of global trade, and urbanization, human life has become significantly easier. People no longer spend a lot of time preparing meals, but quickly get their needs through semi-finished products, fast food or packaged food. But it’s worth thinking seriously about the health effects of modern foods. This article analyzes types of modern food products, technologies of their processing, additives they contain and their positive and negative impact on human health.